Mechanisms Behind the Negative Influence of Single Parenthood on School Performance: Lower Teaching and Learning Conditions?. Issue 7 (3rd October 2017) - Dronkers, Jaap; Veerman, Gert-Jan M.; Pong, Suet-Ling
ABSTRACT: We take a first step toward unravelling the mechanisms behind the negative influence of single parenthood and the proportion of single-parent families on school performance, using 2012 international Program for International Student Assessment (PISA) data. We find that individual truancy of pupils fully explains the relationship between living in a single-mother family and math performance (after controlling for confounding factors, such as parental socioeconomic status). School-level measures of classroom disruption and truancy and individual truancy explain some of the negative effect of the school's concentration of students from single-parent families on individual students' math performance. However, the effect of a school's proportion of single-parent families remains significantly negative on individual performance.